Polymeric simvastatin-loaded microsphere delivery system for bone tissue engineering - Mohamed, Nur Aliana Hidayah (2020)
Bone graft are useful in the treatment of musculoskeletal injuries/diseases including trauma, bone fractures, painful vertebrae, missing teeth, osteosarcoma, and birth defects. The gold standard for bone graft therapies must be osteoconductive, osteogenic and osteoinductive. Different synthetic and natural biomaterials are being investigated for this purpose. The need to find less sophisticated and more patient-friendly alternatives to the bone graft procedure is a driving force behind recent advances in bone tissue engineering.